2020
DOI: 10.14334/jitv.v25i1.2069
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Maternal Genetic Trends for Some Productive and Reproductive Traits in Egyptian Buffaloes

Abstract: This study was done to determine the direct and maternal genetic and phenotypic trends for productive traits such as first lactation milk yield (FLMY, kg), first lactation period (FLP, d) and first lactation daily milk (FLDM, kg), and reproductive traits such as age at first calving (AFC, mo), First days open (FDO, d) and first calving interval (FCI, d). Data were collected over consecutive 25 years (1991 to 2015) of 1104 first lactation of 135 sires and 482 dams maintained at Mahallet Mousa farms of Animal Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
(19 reference statements)
4
2
0
Order By: Relevance
“…This may arise from that AFC depends on puberty reaching and can be influenced by a lesser degree of management practices. The obtained results in this study fall within the range of those reported by other investigators as ranged from 0.11 to 0.45 for AFC (El-Bramony, 2011, andEl-Naser, 2020), from zero to 0.06 for GL on different buffalo breeds (Khalil et al, 1991 andThevamanoharan et al, 2002), from zero to 0.18 for DO (Metry et al,1994 andAbo-Gamil et al, 2017) and from zero to 0.17 for CI (Cockrill, 1974 andAbo-Gamil et al, 2017). Genetic and phenotypic correlations among studied traits are given in Table 4.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This may arise from that AFC depends on puberty reaching and can be influenced by a lesser degree of management practices. The obtained results in this study fall within the range of those reported by other investigators as ranged from 0.11 to 0.45 for AFC (El-Bramony, 2011, andEl-Naser, 2020), from zero to 0.06 for GL on different buffalo breeds (Khalil et al, 1991 andThevamanoharan et al, 2002), from zero to 0.18 for DO (Metry et al,1994 andAbo-Gamil et al, 2017) and from zero to 0.17 for CI (Cockrill, 1974 andAbo-Gamil et al, 2017). Genetic and phenotypic correlations among studied traits are given in Table 4.…”
Section: Resultssupporting
confidence: 92%
“…In contrast, lower than estimated by Ryan et al (2007) of 340 days on African buffalo. Means reported herein for DO and CI fall within the ranges of those obtained for the Egyptian buffaloes as ranged from 120.8 to 250.9 days and from 428 to 539.9 days, respectively (El-Naser, 2020 andAfifi, et al, 1992). This study reflected variation coefficients ranged from 6.98 % to 19.67% except for DO had a higher C.V % of 57.67%, that indicating a large variation among individual buffaloes which can be a good opportunity for this trait to be improved.…”
Section: Resultssupporting
confidence: 81%
“…There were positive genetic correlations among the reproductive traits in this study that ranged from 0.04 (GL-DO) to 0.99 (CI-DO), which revealed that buffalo cows reproduced earlier tended to have shorter GL, CI, DO (Table 4). These results were comparable with the finding of others (Gutierrez et al, 2007;Eaglen et al, 2012;Brzáková et al, 2019;Lopez et al, 2019;Setiaji and Oikawa, 2019;Abu El-Naser, 2020).…”
Section: Resultssupporting
confidence: 93%
“…Comparing our results with existing literature provides a contextual understanding. Abu El‐Naser (2020) conducted a study on Egyptian buffaloes, reporting a lower additive genetic variance (σa2$$ {\sigma}_{\mathrm{a}}^2 $$ = 465.45) but a higher heritability ( h 2 = 0.19) compared with our findings. Kumar and Mandal (2021) in Jersey crossbred cattle observed higher values for both additive genetic variance (σa2$$ {\sigma}_{\mathrm{a}}^2 $$ = 2340.744 to 3835.815) and heritability ( h 2 = 0.16 to 0.25), emphasizing breed‐specific variations.…”
Section: Discussionsupporting
confidence: 45%